Natural History of Afferent Baroreflex Failure in Adults. (13th July 2021) - Lamotte, Guillaume; Coon, Elizabeth A.; Suarez, Mariana D.; Sandroni, Paola; Benarroch, Eduardo E.; Cutsforth-Gregory, Jeremy K.; Mauermann, Michelle L.; Berini, Sarah E.; Shouman, Kamal; Sletten, David; Goodman, Brent P.; Low, Phillip A.; et al.
Abstract : Objective: To describe the natural history of afferent baroreflex failure (ABF) based on systematic review of clinical and laboratory data in patients with a diagnosis of ABF at Mayo Clinic Rochester. Methods: We performed a retrospective chart review of all patients who underwent standardized autonomic reflex testing between 2000 and 2020 and had confirmation of the diagnosis of ABF by an autonomic disorders specialist. Patients were identified using a data repository of medical records. Variables included demographic, all-cause mortality, medications, ABF manifestations, comorbidities, and laboratory (autonomic testing, blood pressure monitoring, echocardiogram, brain imaging, plasma catecholamines, serum sodium level, and kidney function tests). Results: A total of 104 patients with ABF were identified. Head and neck radiation was the most common etiology (86.5%), followed by neck surgery (5.8%) and other causes (7.7%). The most common findings were hypertension (87.5%), fluctuating blood pressure (78.8%), orthostatic hypotension (91.3%), syncope (58.6%), headache (22.1%), and tachycardia (20.2%). Patients commonly received antihypertensives (66.3%), pressor agents (41.3%), or a combination of both (19.2%). The median latency from completion of radiation to ABF was longer compared to the latency in the surgery group ( p < 0.0001). Comorbidities, including complications from neck radiation, were frequently seen and all-cause mortality was 39.4% over a 20-year period. Conclusions: ABF should be suspected in patients with prior head and neck cancer treated by radiation or surgery who present with labile hypertension and orthostatic hypotension. Management may require both antihypertensive and pressor medications. The morbidity and mortality in ABF are high.